Analisis Efektivitas Warna dan Kedalaman Pengoperasian Lampu LED terhadap Hasil Tangkapan Cumi-Cumi (Logilo Chinensis) - Rapi , Nuraeni L; Hasbi , Ibnu Malkan; Rahman, Rahman (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Institut Teknologi dan Bisnis Maritim Balik Diwa, 2023)
Squid is an Indonesian export product that has high economic value, sharing the type of squid which is classified as cuttlefish (Loligo chinensis.). This research aims to determine the length and weight of squid depending on the color of the lights and the depth of the water, the time it takes for the squid to gather in the fishing area, and the level of effectiveness of the squid in different LED lights. Sampling was taken in the waters of North Galesong District, Takalar Regency, with seven repetitions of blue and green lights. This research is included in quantitative research using experimental fishing and data collection using survey methods. The results of the data obtained are described in a comparative descriptive manner. analysis of the pattern of the relationship between the weight and length of the squid mantle obtained a value of W= 1.5629L^0.0017. Correlation value 84.739, contribution of 96.38% and 3.62%. squid caught with LED lights at a depth of 1 meter, 55 fish, and 3 meters, 25 fish. Frequency distribution of the length of squid (Loligo chinensis) in the North Galesong waters, distribution of weight and length of squid mantle at a depth of 1 meter, frequency of squid mantle length between 9.3–11.1 cm, stagnant frequency 15–16.8. Squid weight frequency 27–32g stagnant frequency 81–95g. The depth distribution is three meters, the squid mantle length frequency ranges between 7.5 – 9.3 cm, and the stagnant frequency is 15.1 – 16.9 cm. Squid weight frequency 12–27g, drop frequency 60 – 75 g. Observation results of salinity values ​​in North Galesong waters are 28-31%, pH values ​​are 6-7. Current speed 0.22 m/s. The squid catch was 80 samples, at intervals of 1, 2, and 3 hours, the catch at an interval of 2 hours was a total of 42, at an interval of 3 hours 23, and in 1 hour only 15 squid. The statistical test results show that the results for the two LED light colors are 2.6177, which is smaller than the t-table 2.1788.